High-pressure phase behaviour of the system (CO2 + C.I. Disperse Orange 30 dye) - dos Santos, J.C. (2012)
The dyeing of textile fibres of poly-ethylene terephthalate (PET) in a supercritical medium is an environmentally friendly technological alternative to the conventional water-based dyeing process. In this work, the solubility of the monoazo disperse dye 4-((2,6-dichloro-4-nitrophenyl) azo)-N-(cyanoethyl)-N- (acetoxyethyl) aniline (CAS number 5621-31-4, also known as "C.I. Disperse Orange 30") in supercritical carbon dioxide (SC-CO 2) was experimentally studied within a dye mole fraction range from 6.55·10 -6 to 9.31·10 -6 and over the temperature range from (303.15 to 333.15) K. The resulting measured solid-fluid transition pressures fell in the range from (9.93 to 14.82) MPa. The measurements were performed using the static-synthetic method. The dye solubility in carbon dioxide was found to increase with increasing pressure. The experimental results were correlated with a model that combines the Peng-Robinson equation of state for describing the fluid phase and a standard equation for the fugacity of the pure dye in solid state. The reference state for such equation is the sublimation curve of the pure dye.